Gender, technology, and labor in small-scale aquaculture in Chile - Constantino Villarroel; Katina Roumbedakis; Julia T. Verba; Angelo Araya-Piñones; Gillian B. Ainsworth; Valeria Burgos-Fuster; Nancy Chandía; Niris Cortes; Andrés Hurtado; Veronica Relano; Jaime Aburto; Sebastian Villasante; et al. (Frontiers in Marine Science, 2026)
Small-scale aquaculture (SSA) has been promoted as a “blue transformation” strategy to achieve sustainable development. However, it remains unclear how these initiatives contribute to transforming gender relations in coastal communities. This study examines the case of Caleta Buena (Chile), where an SSA project is being implemented with the technical support of researchers. A qualitative methodology was employed using semi-structured interviews, focus groups, and photographic records, combined with content analysis and Structural Topic Modeling (STM), to analyze the differences between men’s and women’s narratives around the adoption of SSA. The findings highlight that SSA fulfills a dual role: materially, by diversifying production and income, and symbolically, by redefining community and gender roles. The women’s narratives emphasize quality of life and collective well-being, whereas the men’s discourse focuses on organizational strengthening and market integration. Although women gain autonomy and visibility through their participation in the aquaculture project, their empowerment remains partial and ambivalent, rooted in tasks historically associated with femininity. The study’s implications reveal an incipient agency that challenges the symbolic boundaries between masculine and feminine, opening a window of opportunity for more equitable institutional initiatives. The case study demonstrates the need to translate Chilean regulations on gender equality in artisanal fisheries into effective practices within these communities.